2018
DOI: 10.1016/j.freeradbiomed.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein S-nitrosation protects against ischemia reperfusion-induced denervation at neuromuscular junction in skeletal muscle

Abstract: Deterioration of neuromuscular junction (NMJ) integrity and function is causal to muscle atrophy and frailty, ultimately hindering quality of life and increasing the risk of death. In particular, NMJ is vulnerable to ischemia reperfusion (IR) injury when blood flow is restricted followed by restoration. However, little is known about the underlying mechanism(s) and hence the lack of effective interventions. New evidence suggests that mitochondrial oxidative stress plays a causal role in IR injury, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 73 publications
(109 reference statements)
0
30
1
Order By: Relevance
“…Analogously, ischemic insults, which disrupt the perfusion to skeletal muscle, delays the initial response to injury and influences the outcome of muscle regeneration, as demonstrated by the continuous regeneration 56 days following HLI. While previous reports have shown a delayed and prolonged regenerative response to ischemia through centrally nucleated fibers up to day 14 [12], accreted myonuclei up to day 14 [40], and denervation up to day 28 [20], our data indicates that the regeneration of these niche components are sustained for at least 56 days. Nonetheless, in order to discern when these ischemic tissues are fully repaired, further testing with extended time points is required.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Analogously, ischemic insults, which disrupt the perfusion to skeletal muscle, delays the initial response to injury and influences the outcome of muscle regeneration, as demonstrated by the continuous regeneration 56 days following HLI. While previous reports have shown a delayed and prolonged regenerative response to ischemia through centrally nucleated fibers up to day 14 [12], accreted myonuclei up to day 14 [40], and denervation up to day 28 [20], our data indicates that the regeneration of these niche components are sustained for at least 56 days. Nonetheless, in order to discern when these ischemic tissues are fully repaired, further testing with extended time points is required.…”
Section: Discussioncontrasting
confidence: 71%
“…In support of this notion, some of the axonal guidance factors are known to possess angiogenic properties [17], and other well-known angiogenic factors, such as vascular endothelial growth factor (VEGF), guide Schwann cell-mediated peripheral nerve regeneration [18]. As such, when blood flow is restricted in ischemic injury, motor neurons undergo rapid Wallerian degeneration, and their regenerative response is activated [19,20]. Moreover, a recent report showed that the regeneration of the motor neuron and its corresponding neuromuscular synapses are in part linked to an increase in activation of MuSC and myogenesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…MnTnBuOE-2-PyP 5+ blocked mitochondrial ROS to significantly reduce MitoPQ induced motor deficits; suggesting mitochondrial ROS production is the key proximal event. A related corollary: MitoSNO rescues ischemia-reperfusion injury induced denervation by blocking mitochondrial ROS [76] .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a recent study suggests neuromuscular junction alterations (e.g. fragmentation of the acetylcholine receptor cluster on the muscle fibre) do not occur with ageing in human muscle (Jones et al 2017), the results of this recent study are confounded by the source material which largely came from the amputated limbs of individuals with a history of peripheral vascular disease, noting that ischaemia-reperfusion is known to cause neuromuscular junction degeneration (Tu et al 2017;Wilson et al 2018). Indeed, other studies of neuromuscular junction morphology with ageing in human skeletal muscle (Oda, 1984;Wokke et al 1990) have observed similar fragmentation patterns to that seen in rodent models of ageing (Valdez et al 2012).…”
mentioning
confidence: 68%
“…; Wilson et al . ). Indeed, other studies of neuromuscular junction morphology with ageing in human skeletal muscle (Oda, ; Wokke et al .…”
mentioning
confidence: 97%